2010
DOI: 10.3727/096368910x516637
|View full text |Cite
|
Sign up to set email alerts
|

Human Cord Blood-Derived Endothelial Progenitor Cells and Their Conditioned Media Exhibit Therapeutic Equivalence for Diabetic Wound Healing

Abstract: Transplantation of human cord blood-derived endothelial progenitor cells (EPCs) is reported to contribute to neovascularization in various ischemic diseases. However, the possible beneficial role and underlying mechanisms in diabetes-impaired wound healing have been less well characterized. In this study, EPC transplantation stimulated keratinocyte and fibroblast proliferation substantially as early as 3 days after injury, leading to significantly accelerated wound closure in streptozotocin-induced diabetic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 27 publications
8
75
0
Order By: Relevance
“…Similar results have been reported for the treatment of diabetic dermal wounds. The injection of EPC-CM into wounded diabetic mice promoted wound healing and increased neovascularization to a similar extent to EPC transplantation [36]. In the present study, we demonstrated that cerebral ischemic injury was mitigated by the administration of EPC-CM in a mouse stroke model.…”
Section: Discussionsupporting
confidence: 54%
“…Similar results have been reported for the treatment of diabetic dermal wounds. The injection of EPC-CM into wounded diabetic mice promoted wound healing and increased neovascularization to a similar extent to EPC transplantation [36]. In the present study, we demonstrated that cerebral ischemic injury was mitigated by the administration of EPC-CM in a mouse stroke model.…”
Section: Discussionsupporting
confidence: 54%
“…However, the induction of wound closure was not statistically different compared to the control for the remaining time points [23]. There was a report demonstrating that transplantation of endothelial progenitor cells could enhance keratinocyte and fibroblast proliferation, inducing wound closure as early as day 3 posttransplantation [33]. These discrepancies between the rates of wound closure could be due to multiple factors, such as the quantity of the injected cells, the different types of cell, the use of expanded or freshly isolated cells, the engraftment procedure, and the species of mouse.…”
Section: Discussionmentioning
confidence: 99%
“…For the paracrine effect, one study showed that the conditioned medium of the hematopoietic progenitor cell line of DKmix cells could promote angiogenesis within wounds in murine models [27]. Moreover, conditioned media of human CB-derived endothelial progenitor cells have been found to promote keratinocyte, fibroblast and endothelial cell proliferations in a paracrine manner in the same action performed by the injection of endothelial progenitor cells into wounds on diabetic mice [33]. These data demonstrate that the incorporated stem cells release cytokines that act in a paracrine manner to enhance neovascularization, resulting in the remodeling of extracellular matrix and recruitment of circulating stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…2,21,26,27 However, these studies could not predict accurate therapeutic outcomes in humans, as these observations were based in immunodeficient mouse models. In an attempt to provide a more reliable prediction, we assessed the therapeutic efficacy of CB-EPCs and hESCECs after transplantation of these cells into hu-mice after surgically creating hindlimb ischemia ( Figure 4A).…”
Section: Comparison Of Therapeutic Efficacies For Improving Blood Flomentioning
confidence: 99%